Meningkatkan Minat Belajar Siswa Dalam Membaca Al Qur’an Dengan Metode Tartil Berbasis Tekhnologi - Hadijah, Siti; Hayuani , Hayuani; Firmansyah, Firmansyah (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve the interest in reading the Qur’an of 10th grade students at SMK Negeri 1 Tambusai through the implementation of the tartil method based on technology in Islamic Religious Education (PAI) lessons. This study uses the Classroom Action Research (CAR) model with cycles consisting of planning, action, observation, and reflection. The results show that the implementation of the tartil method based on technology can increase students’ activity in Qur’an learning, although 50% of students did not achieve the Minimum Mastery Criteria (KKM) in the first cycle. In the second cycle, there was a significant improvement in students’ activity and understanding, with 80% of students achieving KKM. However, further improvement in learning is needed through more structured strategies and intensive guidance for passive students. This study concludes that the tartil method based on technology can be an effective alternative to improve learning outcomes in PAI at schools.